Analisa dan Perhitungan Baut dan Mur Pada Sambungan Kopling Flens - Afrizal Ammrih Pambudi; Marno Marno; Aa Santosa (Peneliti.net, 2022)
The clutch is a component of a mechanical system to transmit the rotational force of a motor or generating machine to the shaft which is connected to other mechanical components. In the mechanical world there are several types of couplings used in mechanical systems, namely: non-fixed couplings and fixed couplings. the clutch remains a clutch that does not allow it to be released while the engine is still running. This type of clutch is usually connected using bolts. So the stresses that occur in this coupling are usually mostly shear stresses on the bolts. This change focuses on bolts and nuts as a fixed coupling connection. Planning of nuts and bolts on flange couplings is a basic requirement that is really needed in this planning, carried out using experimental methods, by analyzing the dimensions, physical quantities of the planning components of nuts and bolts. Based on the results of calculations from the design of the flange coupling, the following data are obtained: Bolt Type = M20, Pitch Distance = 2.5 mm, Outside diameter (db) = 20 mm